Experimental and Applied Immunotherapy - Medin, Jeffrey.; Medin, Jeffrey.; Fowler, Daniel.; Fowler, Daniel. (Humana Press : Imprint: Humana, 2011)
Immunotherapy is now recognized as an essential component of treatment for a wide variety of cancers. It is an interdisciplinary field that is critically dependent upon an improved understanding of a vast network of cross-regulatory cellular populations and a diversity of molecular effectors; it is a leading example of translational medicine with a favorable concept-to-clinical-trial timeframe of just a few years. There are many established immunotherapies already in existence, but there are exciting new cancer immunotherapies just on the horizon, which are likely to be more potent, less toxic and more cost effective than many therapies currently in use. Experimental and Applied Immunotherapy is a state-of-the-art text offering a roadmap leading to the creation of these future cancer-fighting immunotherapies. It includes essays by leading researchers that cover a wide variety of topics including T cell and non-T cell therapy, monoclonal antibody therapy, dendritic cell-based cancer vaccines, mesenchymal stromal cells, negative regulators in cancer immunology and immunotherapy, non-cellular aspects of cancer immunotherapy, the combining of cancer vaccines with conventional therapies, the combining of oncolytic viruses with cancer immunotherapy, transplantation, and more. The field of immunotherapy holds great promise that will soon come to fruition if creative investigators can bridge seemingly disparate disciplines, such as T cell therapy, gene therapy, and transplantation therapy. This text is a vital tool in the building of that bridge.